Is Experimental Evolution of an Increased Aerobic Exercise Performance in Bank Voles Mediated by Endocannabinoid Signaling Pathway? - Jaromin, Ewa; Sadowska, Edyta T.; Koteja, Paweł (Frontiers in Physiology, 2019)
The level of physical activity achieved in a given situation depends on both physiological abilities and behavioral characteristics (motivation). We used a unique animal model to test a hypothesis that evolution of an increased aerobic exercise performance can be facilitated by evolution of motivation to undertake physical activity, mediated by brain endocannabinoid system. Bank voles (Myodes glareolus) from “aerobic” A lines selected for 22 generations for high swim-induced aerobic metabolism (VO2swim) achieved 65% higher “voluntary maximum” VO2swim than voles from unselected, “control” C lines. In C lines, VO2swim was 24% lower than the maximum forced-running aerobic metabolism (VO2run), while in A lines VO2swim and VO2run were practically the same. Thus, the selection changed both the aerobic capacity and motivation to exercise at the top performance level. We applied a pharmacological treatment manipulation to test a hypothesis that the endocannabinoid signaling pathway 1) affects the voles performance in the aerobic exercise trials, and 2) has been modified in the selection process. Administration of the CB1 receptor agonist (Rimonabant) did not affect the level of metabolism, but administration of the endocannabinoid reuptake inhibitor (AM404) decreased VO2swim both in A and C lines (4%, p=0.03) and tended to decrease VO2run (2%, p=0.07). The significant effect of AM404 suggests the involvement of endocannabinoids in signaling pathways controlling the motivation to be active. However, the response to AM404 did not differ between A and C lines (interaction effect, p≥0.29). Thus, the results did not provide a support to the hypothesis that modification of endocannabinoid signaling have played a role in the evolution of increased aerobic exercise performance in our experimental evolution model system.